Correlation Between Local Air Temperature and the COVID-19 Pandemic in Hubei, China - Cheng-yi Hu; Cheng-yi Hu; Lu-shan Xiao; Hong-bo Zhu; Hong-bo Zhu; Hong Zhu; Li Liu; Li Liu (Frontiers Media S.A., 2021)
Objective: To clarify the correlation between temperature and the COVID-19 pandemic in Hubei.Methods: We collected daily newly confirmed COVID-19 cases and daily temperature for six cities in Hubei Province, assessed their correlations, and established regression models.Results: For temperatures ranging from −3.9 to 16.5°C, daily newly confirmed cases were positively correlated with the maximum temperature ~0-4 days prior or the minimum temperature ~11-14 days prior to the diagnosis in almost all selected cities. An increase in the maximum temperature 4 days prior by 1°C was associated with an increase in the daily newly confirmed cases (~129) in Wuhan. The influence of temperature on the daily newly confirmed cases in Wuhan was much more significant than in other cities.Conclusion: Government departments in areas where temperatures range between −3.9 and 16.5°C and rise gradually must take more active measures to address the COVID-19 pandemic.